2012
DOI: 10.1186/1472-6882-12-260
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-like activity of aqueous extract from Agrimonia pilosa Ledeb. in MCF-7 cells

Abstract: BackgroundPostmenopausal women experience estrogen deficiency-related menopausal symptoms (e.g., hot flashes and mood swings) and a dramatic increase in the incidence of chronic diseases. Although estrogen-replacement therapy (ERT) can reduce mortality from cardiovascular disease and improve osteoporosis and menopausal symptoms, its side effects have limited recent use. This study investigated the estrogen-like activity of aqueous extract from Agrimonia pilosa Ledeb.MethodsThe estrogenic activity of A. pilosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Phytoestrogens are chemical compounds synthesized by plants and are obtained naturally in a wide range of foods, and can have estrogenic effects (25)(26)(27)(28). The authors previously reported that low-density blackcurrant anthocyanins and BCE exhibit phytoestrogenic activity mediated via estrogen receptor α signaling (13).…”
Section: Discussionmentioning
confidence: 99%
“…Phytoestrogens are chemical compounds synthesized by plants and are obtained naturally in a wide range of foods, and can have estrogenic effects (25)(26)(27)(28). The authors previously reported that low-density blackcurrant anthocyanins and BCE exhibit phytoestrogenic activity mediated via estrogen receptor α signaling (13).…”
Section: Discussionmentioning
confidence: 99%
“…A number of estrogen target genes have been shown to be involved in regulating the proliferation of ER-positive breast cancer cells and modulating estrogen sensitivity in a gene-specific manner (2931). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to Carson and Rittmaster, TGF-β activity, which modulates apoptosis, is also influenced by dihydrotestosterone (DHT) [143,144]. More recently, the importance of DHT has been known to act as androgens and to be metabolized to 5α-androstane-3β-17β-diol (3βAdiol), androgens, which are a ligand for estrogen receptor [145][146][147][148][149][150].…”
Section: Discussionmentioning
confidence: 99%